IMPROVING STUDENTS’ READING SKILL THROUGH TEXT BASED INSTRUCTION MODEL OF SECOND SEMESTER STUDENTS OF ENGLISH LANGUAGE EDUCATION STUDY PROGRAM KHAIRUN UNIVERSITY IN ACADEMIC YEAR 2021/2022 - Hamida Jasin; Yetty Yetty (Cakrawala Bahasa, 2022)
This research is intended to find out the implementation of text based instruction model in teaching reading skill, and to find out the improvement of students’ reading  skill through the implementation of text based instruction model. In this study the researchers used functional text used students of second semester of english language education study program Khairun University as the data source of this research. The research instrument used in the form of observation checklist, and test. The data is in the research  are mainly gathered through the use of pre-test, observation, questionnaires, and post test. In analyzing the data, the researchers applied descriptive tehnique. After the data are collocted, they are analyze based on five indicators; scanning for the key words, skimming for the specific information, making inference, looking for topic, understanding paragraph. The result shows that the implementation of text based instruction model through pre-activity, while activity and post activity can improve the students’ speaking skill. The implementation of text based instruction model can improve students’ speaking skill of the second semester students of English language education study program Khairun university. In the pre-test result, in which they formerly did not learn using text based instruction model, the mean of pre-test was 50.05. After they learn English using Small group discussion, the mean  of post test was 75.09